OPTIMIZATION OF THE CHOICE OF ADJUVANT THERAPY IN PATIENTS WITH UTERINE CORPUS CANCER - А. L. Chernyshova; Zh. А. Startseva; А. А. Zatolokina (Сибирский онкологический журнал, 2016)
Despite the large number of studies, including randomized, the role of adjuvant radiotherapy for early-stage uterine corpus cancer remains a matter of debate. We present our results and literature review devoted to the analysis of the effectiveness of new prognostic criteria for cancer of the corpus uteri. The introduction of these markers into routine clinical practice will allow a personalized treatment for patients with stage I uterine corpus cancer.